Lichen sclerosus: evidence that immunological changes occur at all levels of the skin. - Farrell, A; Marren, P; Dean, D; Wojnarowska, F (1999)
An immunohistochemical approach was used to characterize the inflammatory infiltrate in vulval lichen sclerosus, using monoclonal antibodies to CD3, CD4, CD8, CD68 and HLA-DR. Significant numbers of CD4 + and CD8 + lymphocytes were observed in the dermal band of inflammatory cells in approximately equal proportions. Less numerous CD4 + and CD8 + lymphocytes also occurred adjacent to the dermoepidermal junction and occasionally in the lower epidermis. Increased numbers of cells staining with the monocyte/macrophage marker CD68 were also present in the band of inflammatory cells as well as being scattered diffusely throughout the sclerotic region. Expression of HLA-DR in the lichen sclerosus specimens was increased within the inflammatory infiltrate and around blood vessels in the dermis. All the vulval lichen sclerosus specimens also demonstrated some HLA-DR expression around the keratinocytes, suggesting that these keratinocytes might be involved in antigen presentation. We also studied the expression of CD44 and its isoforms 3G5 (marker of V3), 8G5 (marker of V6), 3D2 (marker of V4/5) and IE8 (marker of V8/9). CD44 has been proposed to play a part in lymphocyte homing, cell-matrix interaction (particularly with hyaluronic acid), lymphocyte activation and malignant progression of certain tumours. The epidermis of the lichen sclerosus specimens appeared to demonstrate a greater intensity of staining with the pan-CD44 marker F10-44, and reduced staining with 3G5, 3D2 and IE8 compared with normal skin. Like normal skin, the dermis of the lichen sclerosus specimens did not demonstrate staining with 3G5, 3D2, 8G5 or 1E8, but did show staining with F10-44. However, the pattern of the dermal staining with F10-44 reflected the position of the inflammatory infiltrate and was sparse in the five sections where there was a prominent sclerotic zone, but increased in the three sections where there was a prominent band of inflammation cells. Our results demonstrate evidence of immunological changes at all levels of skin involved by lichen sclerosus, including the epidermis.